2021
DOI: 10.3390/ijgi10060366
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Influencing Factors on the Spatial Variability of SOM in the Red Beds of the Nanxiong Basin of China, Using GIS and Geo-Statistical Methods

Abstract: Understanding the spatial variability of soil organic matter (SOM) is crucial for implementing precise land degradation control and fertilization to improve crop productivity. Studying spatial variability provides a scientific basis for precision fertilization and land degradation control. In this study, geostatistics and classical statistical methods were used to analyze the spatial variability of SOM and its influencing factors under various degrees of land degradation in the red bed area of southern China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…This could be owing to the increase in elevation, the higher soil moisture content, and the lower the decomposition efficiency of the material, resulting in an increase in the soil available potassium content. The content of organic matter and pH decreases with the increase of elevation, which is inconsistent with the results of other studies [50]. It could be caused by the natural environment in the study area.…”
Section: The Influence Of Topographical Factors On Soil Nutrientscontrasting
confidence: 99%
“…This could be owing to the increase in elevation, the higher soil moisture content, and the lower the decomposition efficiency of the material, resulting in an increase in the soil available potassium content. The content of organic matter and pH decreases with the increase of elevation, which is inconsistent with the results of other studies [50]. It could be caused by the natural environment in the study area.…”
Section: The Influence Of Topographical Factors On Soil Nutrientscontrasting
confidence: 99%
“…Land use is one of the essential components of an ecosystem and its changes have a significant impact on soil properties (Deng et al, 2018). Previous study by Yan et al (2021) have shown that there are overall soil pH differences among land use patterns and forest land has the lowest pH. Another study by Wang et al (2020) found that the forest soil system has better water holding capacity and water supply capacity, and the SOC content in the forest is significantly higher than shrubs and grasslands.…”
Section: Effects Of Land Use Patterns On Soil Propertiesmentioning
confidence: 99%
“…Ecological restoration entails the implementation of measures according to local conditions and the use of local materials; the measures must be carried out in a scientific manner [2]. The mud skin of weathered redbed soil is often used to control soil desertification and repair slope; its integrity is an important indicator to measure the repairing effect of the mud [3]. Integrity includes skid, acid, and alkali resistance and compression resistance [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%